Sistem Pengaturan Beban dan Monitoring Berbasis IoT pada Pembangkit Listrik Tenaga Mikrohidro Jenis Turbin Pelton - Salsabila, Syakila; Rifky Zulkarnain, Muhammad; Musa, La Ode; Yusuf Yunus, Muh (Politeknik Negeri Ujung Pandang, 2025)
Microhydro Power Plants (MHPP) are small-scale power generation systems that utilize water energy through head height and water flow rate. This study focuses on the Pelton turbine, an impulse turbine, and the implementation of an Internet of Things (IoT)-based monitoring system to enhance efficiency and operational stability. Fluctuations in voltage due to load variations are common in small-scale MHPP, highlighting the need for effective load regulation. The aim of this research is to explore the principles of load regulation and monitoring systems, as well as to evaluate the efficiency of the Pelton turbine-based MHPP integrated with IoT. The methodology employed is experimental, utilizing a prototype MHPP to test valve openings of 45° and 90° under IoT-based load regulation. The results indicate that system efficiency is inversely related to the load applied. The highest efficiency recorded at a 45° opening was 8.93% with a load of 6 Watts, while the lowest efficiency was 6.69% at a 17 Watt load. For the 90° opening, the highest efficiency was 8.83%, also occurring at a 6 Watt load. These findings underscore the necessity for efficient load management to optimize the performance of Pelton turbine-based MHPP.